Current and future energy and exergy efficiencies in the Iran's transportation sector - Zarifi, F.; Mahlia, T.M.I.; Motasemi, F.; Shekarchian, M.; Moghavvemi, Mahmoud (Elsevier, 2013)
Transportation is the second largest energy consumer sector in Iran which accounts for 24% of total energy consumption in 2009. This large percentage (almost a quarter) of energy consumption necessitates the determination of energy and exergy flows and their respective losses, which will enable the reduction of both energy growth and its consequent environmental impacts in the near future. This paper attempts to analyze and investigate the energy and exergy utilization of the transportation sector in Iran for the period of 1998-2009. Additionally, the total energy consumption in each subsector and the overall energy and exergy efficiencies are predicted via scenario approach. A comparison of the overall energy and exergy efficiencies of Iran with six other countries is also presented. The results show that the overall energy and exergy efficiencies of transportation sector in Iran is higher than China and Norway, while it is lower than Saudi Arabia, Jordan, Turkey, and Malaysia for the year 2000. Road appears to be the most efficient subsector. The overall energy efficiency is determined to be in the range of 22.02% in 1998, to 21.49% in 2009, while the overall exergy efficiency is determine to be in the range of 21.47% in 1998, to 21.19% in 2009. The energy consumption in each subsector is predicted from 2010 to 2035. It was discovered that the overall energy and exergy efficiencies possesses an upward trend during this time period. Finally, some recommendations vis-à-vis the improvement of the energy and exergy efficiencies in Iranian transportation sector in the future was provided and duly discussed.